Occupational accidents relating by workers characteristics, knowledge and attitudes in informal alcohol industry (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: This study aims to determine the relationship of worker characteristics, safety knowledge and attitude of using personal protective equipment with the incident of work accident. Methods: This study is a quantitative research with cross sectional approach. Subjects in this study were all workers of informal alcohol industry amout 42 people. Data were analyzed using Chi- square. Result this study that significant between occupational safety knowledge with occupational accidents (p < 0,05) and this study have significant attitude of using personal protective equipment with occupational accident (p < 0,05). While the variables of education, year work, age there is no correlation with work accident (P > 0,05).  Workers less knowledge of occupational safety affects workplace accidents not due to education level. Workers with the attitude of using personal protective equipment such as boots and gloves have not become a habit so work accidents still occur in informal alcohol industry. Conclusion There is need for training and understanding of the types of accidents ranging from mild to severe and how to control the risk of danger to the working environment independently, as well as increasing the contribution of the community to provide self-protective equipment that has good standards. Regular monitoring provides space for the informal industry to improve production quality